Satisfaction Analysis Of The Bogor Pulo Armyn Community Health Center Website Users Using The End User Computing Satisfaction Method - Hermawan, Yanto; Hidayah, Nurul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Public health center is facility service organizing health​ effort health society and efforts health individual level First with more prioritize effort promotive and preventive , for reach degrees health community in the work area . One of The health centers in Bogor City are: Public health center Pulo Armyn Bogor City, where Public health center the using the website as a media provider information related service Public health center . For know level satisfaction user end to a website, then need did it study about analysis level satisfaction user end from that website. Researcher do analysis related level satisfaction user at the end of the website using the End User Computing Satisfaction Method with 6 indicators in the his that is regarding Content, Accuracy, Format, Ease of Use, Timeliness. Data collection is carried out with spread questionnaire to employees and residents who live there place live in the Bogor City area, distribution questionnaire done for 2 weeks with total respondent data namely 107 users . Data obtained tabulated with compile to in table and calculated magnitude percentage its , validity test and reliability test his with using Rstudio tools. Result of research that has been done showing that 57 users feel satisfied with amount percentage 53.3%. Followed with 34 users feel No satisfied with percentage 31.8 %, 14 users feel very satisfied with amount percentage 13.1% and 2 users feel very not satisfied with amount percentage 1.9%. Keywords : Analysis​ Satisfaction , End User Computing Satisfaction , Website Public health center